A Leap of Academic Faith and Resilience: Nontraditional International Students Pursuing Higher Education in the United States of America - Hunter-Johnson, Yvonne (Journal of International Students, 2021)
International students pursuing higher education in the United States are faced with a multiplicity of challenges such as navigating an unfamiliar educational system, relocating to an unfamiliar country, overcoming negative stereotypes associated with being an educational student, and, in some instances, having to learn a foreign language. Despite such challenges, international students remain motivated to pursue higher education in the United States. This qualitative study, utilizing Schlossberg’s adult transition model as a theoretical framework, explored the lived experiences of 16 international students pursuing higher education in the United States. Emphasis was placed on their transitional experiences in relation to their learning. The major theme that emerged was “major adjustment.” Subthemes that emerged regarding these students’ adjustment included (a) diversity and cultural differences in the learning environment, (b) comparative differences in the learning environment, (c) language barriers, and (d) combatting stereotypes. Implications for theory and practice are discussed.